2010
DOI: 10.1603/me09168
|View full text |Cite
|
Sign up to set email alerts
|

Host Feeding Patterns of <I>Culex</I> Mosquitoes (Diptera: Culicidae) in East Baton Rouge Parish, Louisiana

Abstract: Host feeding patterns were examined for four species of Culex mosquitoes collected from 18 sites in or adjacent to East Baton Rouge Parish, LA, from November 2002 to October 2004. Host DNA from 37 bloodfed Culex coronator Dyar and Knab, 67 bloodfed Cx. salinarius Coquillett, 112 bloodfed Cx. nigripalpus Theobald, and 684 bloodfed Cx. quinquefasciatus Say were identified. The percentages of bloodmeals containing mammalian DNA were 94.6% for Cx. coronator, 82.1% for Cx. salinarius, 66.1% for Cx. nigripalpus, and… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

2
35
1
1

Year Published

2011
2011
2024
2024

Publication Types

Select...
7
1

Relationship

0
8

Authors

Journals

citations
Cited by 37 publications
(39 citation statements)
references
References 43 publications
2
35
1
1
Order By: Relevance
“…nigripalpus in enzootic amplification of WNV may be limited by its seasonality of host-seeking and the high percentage of mammalian blood meals taken by this species. 40 In this study, Cx. nigripalpus was not seen in light traps before July, and 66% of identified blood meals were from mammalian sources (2.7% from humans).…”
Section: Ecology Of West Nile Virus Vectors In Louisianamentioning
confidence: 87%
See 2 more Smart Citations
“…nigripalpus in enzootic amplification of WNV may be limited by its seasonality of host-seeking and the high percentage of mammalian blood meals taken by this species. 40 In this study, Cx. nigripalpus was not seen in light traps before July, and 66% of identified blood meals were from mammalian sources (2.7% from humans).…”
Section: Ecology Of West Nile Virus Vectors In Louisianamentioning
confidence: 87%
“…quinquefasciatus blood meals, but this result, combined with a high percentage of blood meals taken on known avian amplifier hosts, indicated a primary role for this species as an enzootic and epidemic vector. 40 Because Cx. quinquefasciatus was not commonly collected, our results may be most pertinent to understanding enzootic transmission of WNV in rural areas with a paucity of primary vectors such as Cx.…”
Section: Ecology Of West Nile Virus Vectors In Louisianamentioning
confidence: 99%
See 1 more Smart Citation
“…quinquefasciatus blood-feeding behavior in other parts of the United States have found that 52.5% of feeds were mammalian (0.4% human) in Harris County, TX, 20 11.6% mammalian (1.9% human) in southern California, 14 and 40.1% mammalian (7% human) in East Baton Rouge, LA. 29 However, our data on blood meal host preferences need to be interpreted cautiously because they represent a snapshot of host preferences taken during a brief period approximately mid-way through the outbreak. Also, we did not conduct bird or mammal censuses in our study areas to quantify availability of various host species.…”
Section: Discussionmentioning
confidence: 99%
“…1 Recent research has emphasized that some bird species are overused relative to their local availability by vector mosquitoes as blood-meal sources [2][3][4][5][6][7] and that overuse of certain avian species could influence the transmission of pathogens. 8 For example, temporal and spatial patterns of American robin ( Turdus migratorius ) abundance have been associated with variability of the rate of human cases of West Nile virus (WNV) and prevalence of WNV in mosquito populations.…”
Section: Introductionmentioning
confidence: 99%